The impact of social assistance programmes in a pandemic: Evidence from Kenya - Christoph Strupat; Emmanuel Nshakira Rukundo (University of Bonn, Center for Development Research (ZEF), 2022)
This paper examines whether social protection - in the form of existing social assistance programmes - affects measures of household well-being such as poverty, food security and costly risk-coping behaviour during the COVID-19 pandemic. Using primary data from nationally representative, in-person surveys in Kenya allows the exploration of the impacts of major social assistance programmes. Our analysis employs the doubly robust difference-in-differences approach to estimate the impacts of social assistance programmes on common measures of household welfare. We find that social assistance programmes significantly reduce the prevalence of economic shocks and the further impoverishment of beneficiaries during the pandemic. Furthermore, households with social assistance coverage are less likely to sell assets as a coping strategy. Overall, the results suggest that, during a systematic crisis such as a pandemic, pre-existing social assistance schemes can deliver positive impacts in line with the primary goals of social safety nets and prevent households from falling deeper into poverty by preserving their asset base.
Keywords: I32; I38; 330; cash transfers; COVID-19; Kenya